Effect of Dementia on the Use of Drugs for Secondary Prevention of Ischemic Heart Disease - Nicole R. Fowler; Amber E. Barnato; Howard B. Degenholtz; Angela M. Curcio; James T. Becker; Lewis H. Kuller; Oscar L. Lopez (Journal of Aging Research)
Background. Dementia and cardiovascular disease (CVD) are frequently comorbid. The presence of dementia may have an effect on how CVD is treated. Objective. To examine the effect of dementia on the use of four medications recommended for secondary prevention of ischemic heart disease (IHD): angiotensin-converting enzyme inhibitors, beta-blockers, lipid-lowering medications, and antiplatelet medications. Design. Retrospective analysis of data from the Cardiovascular Health Study: Cognition Study. Setting and Subjects. 1,087 older adults in four US states who had or developed IHD between 1989 and 1998. Methods. Generalized estimating equations to explore the association between dementia and the use of guideline-recommended medications for the secondary prevention of IHD. Results. The length of follow-up for the cohort was 8.7 years and 265 (24%) had or developed dementia during the study. Use of medications for the secondary prevention of IHD for patients with and without dementia increased during the study period. In models, subjects with dementia were not less likely to use any one particular class of medication but were less likely to use two or more classes of medications as a group (OR, 0.60; 95% CI, 0.36–0.99). Conclusions. Subjects with dementia used fewer guideline-recommended medications for the secondary prevention of IHD than those without dementia.